The Union Impact on Profits in the Supermarket Industry - Voos, Paula B.; Mishel, Lawrence R. (The Review of Economics and Statistics, 1986)
A number of studies have found that unions lower profits, but controversy continues over whether the union impact is or is not greater in more concentrated markets. This empincal controversy is linked to two underlying issues: whether unions distort capital investment decisions, and the total volume of monopoly profits in the U.S. economy. Research on the supermarket industry reveals that unions lower profits substantially in this sector and that indeed their impact is greater when local markets are more concentrated. Recently there has been an explosion of research concerning the union impact on profits and the associated question of whether or not unions reduce profits more in noncompetitive than competitive sectors (for a review of studies, see Voos and Mishel, 1986). This has become an important empirical issue for a variety of reasons. One concern has been whether unions distort capital investment decisions. Insofar as unions merely capture monopoly rents, as opposed to reducing the rate of return in competitive industries, the presumption is that unions create less distortion. A separate issue has been whether or not previous research has underestimated the extent of total monopoly rents in the U.S. economy. This would occur if observed profits are less than total profits in noncompetitive sectors because in those sectors a portion of monopoly rents is being redistributed to unionized employees. While most studies find that unions lower profits, there is some controversy regarding whether or not unions reduce profits more in industries with less competitive market structures. Freeman (1983) and Karier (1985) both find that unions have a much larger effect in concentrated industries. However, Hirsch and Connolly (1985) question that conclusion and Clark (1984) reports contrary evidence with regard to market share. All previous investigations of this issue utilize manufacturing inter-industry data, cross-sections of predominantly-manufacturing firms, or 2-digit SIC manufacturing industry observations disaggregated by state. This paper reports the results of research designed to ascertain whether unions reduce profits in one relatively homogeneous nonmanufacturing industry, supermarkets, and if their impact is larger when local markets are more concentrated. Lamm (1982) and Marion et al. (1979a and 1979b) have explored the impact of unions and of concentration, respectively, on food prices. Moreover, excellent data on supermarket profits exist. The data give our study several unique qualities. Because observations are on firms in specific geographic markets in a single disaggregate industry, any estimated union profit effect cannot be said to result from a correlation between unionism and unobserved industry specific factors. The study is also the first to be based on evidence from the nonmanufacturing sector. The Data Utilized and the Model Estimated The data on which this research was based were gathered under subpoena by the Joint Economic ComReceived for publication July 8, 1985. Revision accepted for publication October 17, 1985. * University of Wisconsin and Industrial Union Department, AFL-CIO, respectively. Special thanks to Frederick Geithman, for many helpful suggestions and for research assistance, and to Bruce Marion for making the data available to us and for commenting on our results. All opinions, as well as errors, are the authors' own. Funds for a portion of this research came from the University of Wisconsin Graduate School. During a portion of this research, Mishel was affiliated with Cornell University.